The good life of teaching : an ethics of professional practice - Higgins, Chris, 1967- (Malden, MA : Wiley-Blackwell, 2011)
"The Good Life of Teaching extends the recent revival of virtue ethics to professional ethics and the philosophy of teaching. It connects long-standing philosophical questions about work and human growth to questions about teacher motivation, identity, and development. Makes a significant contribution to the philosophy of teaching and also offers new insights into virtue theory and professional ethics. Offers fresh and detailed readings of major figures in ethics, including Alasdair MacIntyre, Charles Taylor, and Bernard Williams and the practical philosophies of Hannah Arendt, John Dewey and Hans-Georg Gadamer. Provides illustrations to assist the reader in visualizing major points, and integrates sources such as film, literature, and teaching memoirs to exemplify arguments in an engaging and accessible way. Presents a compelling vision of teaching as a reflective practice showing how this requires us to prepare teachers differently "--
Machine generated contents note: Preface (Richard Smith) -- Acknowledgements -- Introduction : Why We Need a Virtue Ethics of Teaching. Saints and scoundrels ; A brief for teacherly self-cultivation ; From the terrain of teaching to the definition of professional ethics ; Outline of the argument -- PART I. The Virtues of Vocation : From Moral Professionalism to Practical Ethics -- Chapter 1. Work and Flourishing : Williams' Critique of Morality and its Implications for Professional Ethics. Retrieving Socrates' question ; Modern moral myopia ; What do moral agents want? ; From moral professionalism to professional ethics -- Chapter 2. Worlds of Practice : MacIntyre's Challenge to Applied Ethics. The architecture of MacIntyre's moral theory ; A closer look at internal goods ; The practicality of ethical reflection ; What counts as a practice : The proof, the pudding, and the recipe ; Boundary conditions : Practitioners, managers, interpreters, and fans -- Chapter 3. Labour, Work, and Action : Arendt's Phenomenology of Practical Life. Arendt's Singular Project ; Defining the Deed ; Hierarchy and interdependence in the vita activa ; Praxis in the professions -- Chapter 4. A Question of Experience : Dewey and Gadamer on Practical Wisdom. The constant gardener ; The existential and aesthetic dimensions of vocation ; Our dominant vocation ; Practical wisdom and the circle of experience ; The open question -- PART II. A Virtue Ethics for Teachers : Problems and Prospects -- Chapter 5. The Hunger Artist: Pedagogy and the Paradox of Self-Interest. A blind spot in the educational imagination ; The hunger artist ; The very idea of a helping profession ; This ripeness of self -- Chapter 6. Working Conditions : The Practice of Teaching and the Institution of School. A prima facie case for teaching as a practice ; MacIntyre's Objection ; Schools as surroundings -- Chapter 7. The Classroom Drama : Teaching as Endless Rehearsal and Cultural Elaboration. Education as the drama of cultural renewal ; A false lead ; Teaching as labour, work, and action ; Education, shelter, and mediation ; Teaching as endless rehearsal ; Teaching as cultural elaboration -- Chapter 8. Teaching as Experience : Toward a Hermeneutics of Teaching and Teacher Education. Teaching as vocational environment ; Batch processing, kitsch culture, and other obstacles to teacher vocation ; The syntax of educational claims ; The shape of humanistic conversation ; Horizons of educational inquiry ; Teacher education for practical wisdom -- Index.
"Originally published as volume 44, issues 2 and 3 of The journal of philosophy of education"--T.p. verso.
Includes bibliographical references (p. 283]-303) and index.
Keywords: Teaching -- Moral and ethical aspects; Education -- Moral and ethical aspects; Teaching -- Philosophy; Education -- Philosophy; PHILOSOPHY / History & Surveys / General